Early Modern Metaphysical Literature - Holmes, Michael Morgan. author. aut Link
X, 204 p. 5 illus.
Keywords: Early Modern Metaphysical Literature illuminates now-obscured aspects of cultural negotiation and denaturalization germane to numerous Metaphysical texts. Examining poetry and prose by Donne, Marvell, Lanyer, Crashaw, and Edward Herbert, this book challenges readers to recognize the provocative strangeness of these writings in their original contexts and today.